Can We Still Stop the End of Internationalization? - Latorre, Paulina; Brandenburg, Uwe; de Wit, Hans (International Higher Education, 2024)
Twelve years ago IHE published the essay “The End of Internationalization.” It critiqued the focus on its commercialization and made a plea to rethink and redefine the way we look at the internationalization of higher education. This essay looks back and notices that things have not changed substantially and places the debate in the current context of multiple crises. It advocates the need for an active personalized internationalization with emphasis on our own social responsibility.